Nitrogen-doped novolac epoxy resin-based hard carbon as well as preparation method and application thereof

Through the mixing and carbonization process of phenolic epoxy resin and glycidylamine epoxy resin, high capacity and high magnification nitrogen-doped hard carbon materials were prepared, which solved the problems of complex processes, low carbonization yield and high cost in the prior art, and achieved high performance hard carbon materials suitable for sodium ion batteries.

CN120221646APending Publication Date: 2025-06-27WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202311804257.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-26
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

The existing preparation methods of nitrogen-doped hard carbon materials have problems such as complex processes, low carbonization yield and high cost, and it is difficult to improve the capacity and rate performance of hard carbon at the same time.

Method used

The phenolic epoxy resin is mixed with glycidylamine epoxy resin, and carbonized in an inert atmosphere after alkaline catalytic polymerization, curing, and pulverization, to prepare a nitrogen-doped phenolic epoxy resin-based hard carbon material.

Benefits of technology

It realizes the preparation of hard carbon materials with high capacity and high magnification, with simple process, high carbonization yield and low cost, and is suitable for negative electrode materials for sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004629787510000111
    Figure BDA0004629787510000111
  • Figure HDA0004629787540000011
    Figure HDA0004629787540000011
  • Figure HDA0004629787540000012
    Figure HDA0004629787540000012
Patent Text Reader

Abstract

The invention provides a preparation method of nitrogen-doped novolac epoxy resin-based hard carbon, which comprises the following steps: polymerizing a phenol monomer and an aldehyde monomer in the presence of a basic catalyst, uniformly mixing with glycidyl amine epoxy resin, curing, crushing and carbonizing to obtain a nitrogen-doped hard carbon material. Due to effective nitrogen doping, the sodium ion battery assembled by using the hard carbon material has the characteristics of high reversible specific capacity and high rate performance; the glycidyl amine epoxy resin is high in epoxy group content, can be cured without adding a curing agent after being mixed with the phenolic resin, and can anchor free phenol in the phenolic resin, so that the carbon yield is increased. The preparation method of the nitrogen-doped novolac epoxy resin-based hard carbon provided by the invention has the advantages of simple process, high carbonization yield and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sodium-ion batteries, and particularly to a preparation method of nitrogen-doped phenolic epoxy resin-based hard carbon and its application in sodium-ion batteries. Background Art

[0002] Sodium-ion batteries show broad application prospects in the fields of power and energy storage due to their advantages such as cost, safety, and low-temperature performance. Hard carbon materials are the most widely used anode materials in sodium-ion batteries. Resin materials have the advantages of adjustable precursor composition, morphology, and structure, and simple carbonization process, and are the most promising hard carbon precursors for large-scale production and application. Among many polymer materials, phenolic resin has become the most concerned resin precursor because of its low cost, mature preparation process, and high residual carbon rate.

[0003] Multiple methods have been proposed to further improve the performance of resin-based hard carbon. Among them, nitrogen doping can improve both the capacity and rate performance of hard carbon, and has been widely studied. As an amorphous carbon material, hard carbon is usually composed of a large number of disordered graphite microcrystals and amorphous regions. The electrochemical charge-discharge curve of conventional hard carbon generally consists of two parts: a plateau region (below 0.1V) and a slope region (above 0.1V). Generally, it is considered that the capacity of the slope region corresponds to the adsorption of sodium ions on the surface, defect sites, and functional groups, and the capacity of the slope region is for the intercalation of sodium ions into the graphitized carbon layer and micropore filling. It has been found that nitrogen elements in carbon materials have higher activity, can provide more sodium ion adsorption sites, thus increasing the capacity of the slope region, and nitrogen elements in the graphite microcrystal region can expand the carbon layer spacing, facilitating the diffusion of sodium ions between layers, thereby increasing the capacity of the plateau region. In addition, nitrogen doping can significantly improve the electronic conductivity of hard carbon materials and has an obvious promoting effect on the rate performance.

[0004] Nitrogen doping can be achieved by various methods. CN116621159A discloses a method in which nitrogen-doped hard carbon materials are obtained by subjecting hard carbon to plasma ball milling in a nitrogen-filled ball milling tank. However, for the gas-phase nitrogen doping method, it is difficult for nitrogen to diffuse into the interior of hard carbon materials, and the nitrogen doping effect is not obvious. CN115249799A uses hard carbon powder mixed with nitrogen source powders such as urea, melamine, and aniline for secondary carbonization for nitrogen doping. The process route is extended, and hydrogen cyanide, a toxic gas, may be generated during the decomposition of organic carbon sources. CN116477605A synthesizes aminoaldehyde resin using phenylenediamine, hexamethylenetetramine, and polyoxyethylene polyoxypropylene ether block copolymer, and obtains nitrogen-containing hard carbon materials by one-step carbonization. The disadvantage of this method is that the synthesized aminobenzene resin introduces more straight-chain carbon than phenolic resin, and carbon chain breakage and movement are more likely to occur during the cracking process, resulting in a lower carbonization yield. Summary of the Invention

[0005] The present invention provides a method for preparing nitrogen-doped phenolic epoxy resin-based hard carbon. After polymerization of phenolic monomers and aldehyde monomers under an alkaline catalyst, they are uniformly mixed with glycidylamine epoxy resin, cured, pulverized, and then carbonized to obtain a nitrogen-doped hard carbon material. The present invention overcomes the disadvantages of the foregoing methods, obtains a hard carbon material with high capacity and high rate performance, and has the advantages of simple process, high carbonization yield, and low cost.

[0006] The present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a nitrogen-doped phenolic epoxy resin-based hard carbon material, comprising the following steps:

[0008] 1) Dissolve phenolic monomers and aldehyde monomers in solvent (a), add an alkaline catalyst, heat and stir to polymerize to obtain a viscous phenolic resin liquid, add solvent (b), and adjust the solid content of the phenolic resin to 1-99%;

[0009] 2) Stir and mix the phenolic resin with glycidylamine epoxy resin to obtain a phenolic epoxy resin;

[0010] 3) Remove the solvent from the mixed resin, cure it, and then pulverize it;

[0011] 4) Carbonize the obtained powdery phenolic epoxy resin precursor in an inert atmosphere to obtain a nitrogen-doped phenolic epoxy resin-based hard carbon material.

[0012] Preferably, in step 1), the phenolic monomer is selected from one or more of phenol, resorcinol, catechol, cresol, xylenol, methoxyphenol, guaiacol, eugenol, bisphenol A, biphenol, naphthol, aminophenol, and polyphenolic compounds such as flavonoids and lignans.

[0013] Preferably, in step 1), the aldehyde monomer is selected from one or more of formaldehyde, paraformaldehyde, C2-C5 alkyl aldehydes, aromatic aldehydes, and furfural.

[0014] Preferably, in step 1), the alkaline catalyst is selected from one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, and ammonia water.

[0015] Preferably, in step 1), the phenolic monomer and the aldehyde monomer are fed in a molar ratio of 1:1-2, and more preferably, the molar ratio of the phenolic monomer to the aldehyde monomer is 1:1.3-1.5.

[0016] Preferably, in step 1), the mass ratio of the alkaline catalyst to the phenolic monomer is 1-50:100, and more preferably, the mass ratio of the catalyst to the phenolic monomer is 1-10:100.

[0017] Preferably, in step 1), the solvent (a) is selected from water, ethanol, glycerol, ether, and acetone.

[0018] Preferably, the solvent (b) in the step 1) is selected from ethanol, methanol, ethylene glycol, propylene glycol, dipropylene glycol, glycerol, acetone, benzene and toluene.

[0019] Preferably, the glycidylamine epoxy resins in the step 2) include one or more of triglycidyl isocyanurate (TGIC), triglycidyl p-aminophenol (TGPAP), tetraglycidyl diaminodiphenylmethane (TGDDM), diisopropylidene phenylene type tetraglycidylamine (TGBAP), tetramethyl isopropylidene phenylene tetraglycidylamine (TGMBAP), N,N,N',N'-tetraglycidyl-4,4-diaminodiphenylmethane (TCDN), N,N,N',N'-tetraglycidyl-2,2-bis[4-(4-aminophenoxy)phenyl]propane (TGBAPOPP), N,N,N',N'-tetraglycidyl-4,4'-methylenedi-o-toluidine (TGMDT) and 4,4'-diaminodiphenyl ether tetraglycidylamine (TGDAE).

[0020] Preferably, the mass ratio of the glycidylamine epoxy resin to the phenolic resin in the step 2) is 1-100:100. Further preferably, the mass ratio of the epoxy resin to the phenolic resin is 5-20:100.

[0021] It is worth mentioning that no additional curing agent is added for the curing of the phenolic epoxy resin in the step 3).

[0022] Preferably, the curing methods in the step 3) include at least one of thermal curing (curing temperature 80-250 °C); electron beam curing (electron beam energy 50-300 keV) and microwave curing (microwave curing microwave frequency 900 MHz-2450 MHz, power 50-500 W); the curing time is 0.1-24 h; further preferably, the thermal curing time is 2-24 h, the electron beam curing time is 0.1-1 h; the microwave curing time is 0.1-1 h.

[0023] Preferably, the crushing methods in the step 3) include at least one of mechanical crushing, ball milling and air flow crushing. The particle size D50 of the crushed resin precursor is 1-100 μm. More preferably, the particle size D50 of the crushed resin precursor is 5-20 μm.

[0024] Preferably, the inert atmosphere in the step (4) is nitrogen or argon, the carbonization temperature is 1000-1600 °C, the heat preservation time is 1-5 h, and the heating rate is 1-10 °C / min.

[0025] In the second aspect, the present invention also provides a nitrogen-doped phenolic epoxy resin-based hard carbon material:

[0026] The size of the hard carbon material is 1-100 μm, the nitrogen element content of the hard carbon material is 0.01-10 wt%, and the nitrogen element exists in three forms in the hard carbon material structure: pyridine nitrogen, pyrrole nitrogen and graphitic nitrogen.

[0027] Thirdly, the present invention also provides an application of the nitrogen-doped phenolic epoxy resin-based hard carbon material in a negative electrode sheet.

[0028] Fourthly, the present invention provides a negative electrode sheet, which includes the hard carbon material, a conductive agent, a binder and a current collector.

[0029] Finally, the present invention provides a sodium ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and a sodium salt electrolyte solution.

[0030] The sodium salt electrolyte solution in the sodium ion battery contains an electrolyte sodium salt and an organic solvent. Among them, the sodium salt is selected from sodium hexafluorophosphate (NaPF6) or sodium perchlorate (NaClO4), etc.; the organic solvent is selected from one or more of ethylene glycol dimethyl ether (DME), ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC).

[0031] Compared with the existing technology, the beneficial effects of the present invention are as follows:

[0032] In the present invention, phenolic epoxy resin is prepared by mixing liquid phenolic resin and liquid glycidylamine epoxy resin. Nitrogen atoms are evenly distributed inside the resin, and the nitrogen doping amount can be flexibly changed by adjusting the addition amount of epoxy resin; after the resin is cured, nitrogen-doped hard carbon material can be obtained by one-time carbonization, and the process is simple; the present invention uses glycidylamine epoxy resin, which has a high epoxy group equivalent and has more reactive sites. The epoxy group attacks the phenolic hydroxyl group on the phenolic resin to achieve cross-linking without adding a curing agent. During the carbonization process, the highly cross-linked three-dimensional network structure is maintained, and the movement and directional growth of the carbon layer are inhibited, resulting in a hard carbon structure with graphite microcrystals and nano micropores.

[0033] Due to the high steric hindrance and rigid structure of the benzene ring, the movement of carbon atoms in the phenolic resin is blocked. Therefore, compared with resins with a linear carbon structure such as polyacrylonitrile, the phenolic resin has a higher carbon residue rate after high-temperature carbonization; however, during the synthesis process of phenolic resin, the phenolic monomer cannot be completely polymerized, and usually, phenolic resin contains 5-10 wt% of free phenol. These carbon atoms are difficult to be retained in the structure during the carbonization process; the epoxy group in the epoxy resin can fix the residual free phenol in the phenolic resin and cross-link with the main structure of the phenolic resin, which can further improve the carbonization yield of the phenolic resin.

[0034] The nitrogen-doped hard carbon material described in the present invention has the characteristics of high carbonization yield, low cost, and mature process. The sodium-ion battery prepared using this hard carbon material has high capacity, long cycle life, and excellent rate performance. Description of the Drawings

[0035] Figure 1 SEM image of the nitrogen-doped phenolic epoxy resin-based hard carbon prepared in Example 1.

[0036] Figure 2 TEM image of the nitrogen-doped phenolic epoxy resin-based hard carbon prepared in Example 1.

[0037] Figure 3 Charge-discharge curve of the sodium-ion half-cell prepared with the nitrogen-doped phenolic epoxy resin-based hard carbon prepared in Example 1. Detailed Description of the Invention

[0038] The present invention will be further described below in conjunction with the embodiments. It should be noted that the embodiments do not constitute a limitation on the scope of protection required by the present invention.

[0039] Raw materials and sources:

[0040] Phenol (≥99.0% (GC)), 108-95-2, Sigma Aldrich;

[0041] Paraformaldehyde (granular, 95%), 30525-89-4, Sigma Aldrich;

[0042] 3-Aminophenol (98%), 591-27-5, Sigma Aldrich;

[0043] Bisphenol A (97%), 80-05-7, Sigma Aldrich;

[0044] Sodium hydroxide (reaction grade, ≥98.0%), 1310-73-2, Sigma Aldrich;

[0045] Ethanol (chromatographic grade), 64-17-5, Sigma Aldrich;

[0046] N,N,N,N,-tetraglycidyl-4,4-diaminodiphenylmethane TCDN (epoxy equivalent 110 - 130 g / mol), 28768-32-3, Jiangsu Taitel;

[0047] Triglycidyl p-aminophenol TGPAP (epoxy equivalent 100 - 115 g / mol), 5026-74-4, Jiangsu Taitel;

[0048] Polyacrylonitrile (powder, average Mw 150,000), 25014-41-9, Sigma Aldrich.

[0049] Test method:

[0050] Characterization of morphology and structure:

[0051] Instrument: Hitachi S4800 scanning electron microscope (SEM), FEI Tecnai G2F high-resolution transmission electron microscope (HRTEM). Calculation of residual carbon rate:

[0052] Weigh the mass of the resin precursor powder before carbonization and record it as W0. The mass of the hard carbon powder after carbonization is W1. The residual carbon rate is W1 / W0 * 100%.

[0053] Characterization of nitrogen element content in hard carbon powder:

[0054] Instrument: VELP-EMA502 CHNS elemental analyzer;

[0055] Principle: The sample is burned in an oxygen atmosphere. The nitrogen element in the hard carbon is converted into nitrogen oxides in gaseous form, reduced to nitrogen by highly active copper powder, and the gas flow is separated by a gas chromatography column and reaches the TCD detector.

[0056] Electrochemical performance:

[0057] Mix the above resin-based hard carbon material, conductive carbon black and styrene-butadiene rubber evenly according to the mass ratio of 9:0.5:0.5, add an appropriate amount of deionized water to make a negative electrode slurry, and coat it on an aluminum foil current collector. After complete drying, a negative electrode plate is made. Using a sodium metal sheet as the counter electrode, a glass microfiber as the separator, a 1M NaPF6 EC:DEC (1:1 vol%) solution as the electrolyte, 2 wt% FEC as the film-forming additive, and the prepared negative electrode plate, an assembled button cell is used for electrochemical performance testing. Charge and discharge are carried out at rates of 0.1C and 2C, and the test voltage range is 0 - 2V.

[0058] Example 1

[0059] Preparation of phenolic resin:

[0060] Weigh 47 g of phenol and 20 g of deionized water, add them to a 150 ml three-necked flask, heat to 50 °C and stir until the phenol is completely dissolved in water; add 27.5 g of paraformaldehyde and stir until the system is homogeneous, then add 3.0 g of sodium hydroxide, raise the temperature to 75 °C, and continue to react for 2 h. Remove the solvent by vacuum distillation at 90 °C to obtain a viscous reddish-brown phenolic resin. After cooling to room temperature, add anhydrous ethanol to adjust the solid content of the phenolic resin to 70%.

[0061] Preparation of phenolic epoxy resin:

[0062] Take 70 g of the above phenolic resin ethanol solution (phenolic resin content 50 g) and 5 g of N,N,N,N,-tetraglycidyl-4,4-diaminodiphenylmethane (TCDN, CAS: 28768-32-3, epoxy equivalent 130 g / mol), stir at 60 °C for 1 h to mix evenly; heat the above resin liquid to 175 °C to remove ethanol, and keep warm for 6 h to obtain a blocky dark brown solid phenolic epoxy resin.

[0063] Preparation of hard carbon based on phenolic epoxy resin:

[0064] Crush the above blocky resin into irregularly shaped powder with an average D50 particle size of 10 μm; transfer the above powder into a carbonization reactor under a nitrogen atmosphere, heat it to 1200 °C at a heating rate of 10 °C / min, and keep warm for 1 h to obtain hard carbon powder, the morphology of which is as Figure 1 shown.

[0065] Example 2

[0066] This example provides a preparation method of nitrogen-doped phenolic reduced resin-based hard carbon. The preparation method is basically the same as that of Example 1, except that: the phenolic monomer for synthesizing the phenolic resin is bisphenol A, and the molar ratio of bisphenol A to paraformaldehyde is 1:1.5.

[0067] Example 3

[0068] This example provides a preparation method of nitrogen-doped phenolic reduced resin-based hard carbon. The preparation method is basically the same as that of Example 1, except that: the phenolic monomer for synthesizing the phenolic resin is aminophenol, and the molar ratio of aminophenol to paraformaldehyde is 1:1.5.

[0069] Example 4

[0070] This example provides a preparation method of nitrogen-doped phenolic reduced resin-based hard carbon. The preparation method is basically the same as that of Example 1, except that: the mass ratio of epoxy resin to phenolic resin is 1:5.

[0071] Example 5

[0072] This example provides a preparation method of nitrogen-doped phenolic reduced resin-based hard carbon. The preparation method is basically the same as that of Example 1, except that: the mass ratio of epoxy resin to phenolic resin is 1:20.

[0073] Example 6

[0074] This embodiment provides a method for preparing nitrogen-doped phenolic-reduced resin-based hard carbon. The preparation method is basically the same as that of Example 1, except that: the epoxy resin is triglycidyl p-aminophenol (TGPAP, CAS: 5026-74-4, epoxy equivalent 115 g / mol), and the mass ratio of the epoxy resin to the phenolic resin is 1:10.

[0075] Example 7

[0076] This embodiment provides a method for preparing nitrogen-doped phenolic-reduced resin-based hard carbon. The preparation method is basically the same as that of Example 1, except that: the liquid phenolic epoxy resin is cured by the microwave method. The equipment is the Shunde Xianhua E100-EA microwave reactor, the microwave frequency is 2450 MHz, the power is 500 W, and the microwave treatment time is 10 minutes.

[0077] Example 8

[0078] This embodiment provides a method for preparing nitrogen-doped phenolic-reduced resin-based hard carbon. The preparation method is basically the same as that of Example 1, except that: the carbonization program is to heat to 1400 °C at a rate of 10 °C / min and hold for 1 h.

[0079] Comparative Example 1

[0080] In Comparative Example 1, the phenolic resin is directly carbonized without nitrogen doping treatment. The implementation process is as follows.

[0081] Weigh 47 g of phenol and 20 g of deionized water, add them to a 150 ml three-necked flask, heat to 50 °C and stir until the phenol is completely dissolved in water; add 27.5 g of paraformaldehyde and stir until the system is homogeneous, then add 3.0 g of sodium hydroxide, raise the temperature to 75 °C, and continue to react for 2 h. The solvent is removed by vacuum distillation at 90 °C to obtain a viscous reddish-brown phenolic resin. The above resin is heated to 175 °C for curing to obtain a blocky dark brown resin. The above blocky resin is crushed into irregular-shaped powder with an average D50 particle size of 10 μm; the above powder is transferred into a carbonization reactor under a nitrogen atmosphere and heated to 1200 °C at a heating rate of 10 °C / min and held for 1 h to obtain hard carbon powder.

[0082] Comparative Example 2

[0083] Take 50 g of polyacrylonitrile (molecular weight 150000, powder), and in a carbonization reactor under a nitrogen atmosphere, heat to 1200 °C at a heating rate of 10 °C / min and hold for 1 h to obtain hard carbon powder.

[0084] The test results are shown in the following table:

[0085]

[0086] As can be seen from the above table: In Examples 1 to 8, nitrogen-doped phenolic epoxy resin precursors were used. Compared with the polypropylene precursor, the residual carbon rate after carbonization was significantly improved; the assembled sodium-ion batteries all showed higher reversible capacity, first-cycle efficiency, and rate performance than the phenolic resin-based hard carbon of Comparative Example 1 without nitrogen doping, indicating an obvious improvement effect of nitrogen doping through epoxy resin on the residual carbon rate and electrochemical performance.

Claims

1. A preparation method of a nitrogen-doped phenolic epoxy resin-based hard carbon material, comprising the following steps: 1) Dissolve a phenolic monomer and an aldehyde monomer in solvent (a), add a basic catalyst, heat and stir to polymerize to obtain a viscous phenolic resin liquid, add solvent (b), and adjust the solid content of the phenolic resin to 1-99%; 2) Stir and mix the phenolic resin with a glycidylamine epoxy resin to obtain a phenolic epoxy resin; 3) Remove the solvent from the mixed resin, cure it, and then crush it; 4) Carbonize the obtained powdery phenolic epoxy resin precursor in an inert atmosphere to obtain a nitrogen-doped phenolic epoxy resin-based hard carbon material.

2. The preparation method according to claim 1, characterized in that, In step 1), the phenolic monomer is selected from one or more of phenol, resorcinol, catechol, cresol, xylenol, methoxyphenol, guaiacol, eugenol, bisphenol A, biphenol, naphthol, aminophenol, and polyphenolic compounds such as flavonoids and lignans; and / or, in step 1), the aldehyde monomer is selected from one or more of formaldehyde, paraformaldehyde, C2-C5 alkyl aldehydes, aromatic aldehydes, and furfural; and / or, in step 1), the basic catalyst is selected from one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, calcium hydroxide, and ammonia water.

3. The preparation method according to claim 1 or 2, characterized in that, In step 1), the phenolic monomer and the aldehyde monomer are fed in a molar ratio of 1:1-2, and more preferably, the molar ratio of the phenolic monomer to the aldehyde monomer is 1:1.3-1.5; and / or, in step 1), the mass ratio of the basic catalyst to the phenolic monomer is 1-50:100, and more preferably, the mass ratio of the catalyst to the phenolic monomer is 1-10:

100.

4. The preparation method according to any one of claims 1 to 3, characterized in that, The glycidylamine epoxy resin in step 2) includes one or more of triglycidyl isocyanurate (TGIC), triglycidyl p-aminophenol (TGPAP), tetraglycidyl diaminodiphenylmethane (TGDDM), diisopropylidene phenylene type tetraglycidylamine (TGBAP), tetramethyl isopropylidene phenylene tetraglycidylamine (TGMBAP), N,N,N',N'-tetraglycidyl-4,4-diaminodiphenylmethane (TCDN), N,N,N',N'-tetraglycidyl-2,2-bis[4-(4-aminophenoxy)phenyl]propane (TGBAPOPP), N,N,N',N'-tetraglycidyl-4,4'-methylenedi-o-toluidine (TGMDT), and 4,4'-diaminodiphenyl ether tetraglycidylamine (TGDAE).

5. The preparation method according to any one of claims 1-4, characterized in that, In step 2), the mass ratio of the glycidylamine epoxy resin to the phenolic resin is 1-100:100, and further preferably, the mass ratio of the epoxy resin to the phenolic resin is 5-20:

100.

6. The preparation method according to any one of claims 1-5, characterized in that, The curing method in step 3) includes at least one of thermal curing, electron beam curing, and microwave curing; preferably, the curing time is 0.1-24 h.

7. The preparation method according to any one of claims 1-6, characterized in that, The pulverization method in step 3) includes at least one of mechanical pulverization, ball milling, and jet milling. The particle size D50 of the pulverized resin precursor is 1 to 100 μm, and more preferably, the particle size D50 of the pulverized resin precursor is 5 to 20 μm; and / or, in step (4), the carbonization temperature is 1000 to 1600 °C, the heat preservation time is 1 to 5 h, and the heating rate is 1 to 10 °C / min.

8. The nitrogen-doped phenolic epoxy resin-based hard carbon material prepared by the preparation method according to any one of claims 1-7, wherein the size of the hard carbon material is 1 to 100 μm, and the nitrogen element content of the hard carbon material is 0.01 to 10 wt%.

9. Application of the nitrogen-doped phenolic epoxy resin-based hard carbon material prepared by the preparation method according to any one of claims 1-7 or the nitrogen-doped phenolic epoxy resin-based hard carbon material according to claim 8 in a negative electrode tab.

10. A negative electrode tab, which comprises the nitrogen-doped phenolic epoxy resin-based hard carbon material prepared by the preparation method according to any one of claims 1-7 or the nitrogen-doped phenolic epoxy resin-based hard carbon material according to claim 8, a conductive agent, a binder, and a current collector.

Citation Information

Patent Citations

  • Rosin-based nitrogen-doped coated hard carbon negative electrode material of sodium-ion battery and preparation method thereof

    CN115249799A

  • Preparation method of in-situ nitrogen-doped micron carbon sphere material and sodium ion battery pack

    CN116477605A

Cited By

  • Resin-based hard carbon microspheres and preparation method thereof

    CN118164468A